2006
DOI: 10.1590/s0100-41582006000600011
|View full text |Cite
|
Sign up to set email alerts
|

Dimorfismo de ascósporos em Glomerella cingulata f.sp. phaseoli

Abstract: O objetivo deste trabalho foi caracterizar linhagens de Glomerella cingulata f. sp. phaseoli quanto ao crescimento micelial, formação de peritécio e dimorfismo de ascósporos. Foram avaliadas quatro linhagens nos meios de cultura de folhas de feijoeiro e meio M3 e em condições com e sem fotoperíodo. O comprimento dos ascósporos da linhagem normal e da mutante foi determinado. Houve diferença significativa quanto ao crescimento micelial e tamanho dos ascósporos. Constatou-se, pela primeira vez, em Glomerella cin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
1
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
3
1
0
1
Order By: Relevance
“…These values are in agreement with data described in the literature for the species C. truncatum derived from different hosts (Damm et al, 2009). The size of the ascopores of the strains G43-2 (21.84 x 7.69 µm) and G8-1 (22.59 x 9.3 µm) is in agreement with the data described previously in the literature for the species G. cingulata f. spp phaseoli (Castro et al, 2006;Souza et al, 2007); however, these values are higher than those reported by Kimati and Galli (1970) and Rodrigues-Guerra et al (2005).…”
Section: Discussionsupporting
confidence: 92%
“…These values are in agreement with data described in the literature for the species C. truncatum derived from different hosts (Damm et al, 2009). The size of the ascopores of the strains G43-2 (21.84 x 7.69 µm) and G8-1 (22.59 x 9.3 µm) is in agreement with the data described previously in the literature for the species G. cingulata f. spp phaseoli (Castro et al, 2006;Souza et al, 2007); however, these values are higher than those reported by Kimati and Galli (1970) and Rodrigues-Guerra et al (2005).…”
Section: Discussionsupporting
confidence: 92%
“…The dimensions of allantoid ascospores were similar to those reported by Castro et al (2006) and Barcelos et al (2014). Castro et al (2006) also found dwarf ascospores of similar dimensions to those found for amygdaliform ascospores.…”
Section: Discussionsupporting
confidence: 89%
“…The dimensions of allantoid ascospores were similar to those reported by Castro et al (2006) and Barcelos et al (2014). Castro et al (2006) also found dwarf ascospores of similar dimensions to those found for amygdaliform ascospores. These authors reported the presence of ascospore dimorphism from the observation of a sector formed in a colony of C .…”
Section: Discussionsupporting
confidence: 89%
“…phaseoli ” ( e.g. Castro et al 2006 ) and Glomerella lindemuthiana ( e.g. Rodríguez-Guerra et al 2005 , as G. lindemuthianum ) have been used for the teleomorph of Colletotrichum lindemuthianum in the recent literature, the two names placed in synonymy by Sutton ( 1992 ).…”
Section: Resultsmentioning
confidence: 99%